If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(4x + 1) = -116 Reorder the terms: -4(1 + 4x) = -116 (1 * -4 + 4x * -4) = -116 (-4 + -16x) = -116 Solving -4 + -16x = -116 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -16x = -116 + 4 Combine like terms: -4 + 4 = 0 0 + -16x = -116 + 4 -16x = -116 + 4 Combine like terms: -116 + 4 = -112 -16x = -112 Divide each side by '-16'. x = 7 Simplifying x = 7
| -4x+3x-4=0 | | 7/x-1=0 | | -216=-6(4a+8) | | 2x-7=10x+8 | | -35+y=-12 | | 8m=m+35 | | -12t=-108 | | 12-v=45 | | X-27=59 | | a(n)=-4n+13 | | 10+y=79 | | 2x^2+32x=72 | | 6(3b+2)+2=b-20 | | X/2*30=1000 | | -6+12x=102 | | 5x^2+5y^2-6x-6y+5=0 | | -27+8=-12+c+20 | | 54b+72=252 | | -14+x=-22 | | [v-3]=-7 | | 8b+4=92 | | -83=4(1-4b)-7 | | 6+3x=6-6x | | -13c+7=-32 | | -3(x-8)=5(x+8) | | -7(2n-2)+2=100 | | 8y-12=52 | | 37+5=35+7 | | (f+9)=39 | | -11(-x+10)=-(-x-30) | | 5(f-32)=180 | | X-1=9x+7 |